Construction of New Coefficient of Variation Control Chart based on Median Absolute Deviation - Dashty Ismail Jamil; Saleh, Dlshad Mahmood Saleh; Kamaran Hassan Ahmed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Scale estimators are very important in many statistical applications. A robust estimator is an estimator which is insensitive to changes in the underlying distribution and also resistant against the presence of outliers. Several authors have worked on robust control charts and several robust measures are experimented in process control. Monitoring the coefficient of variation (C.V) is a successful approach to Statistical Process Control when the process mean and standard deviation are not constant. In recent years the (C.V) has been investigated by many researchers as the monitored statistic for several control charts. The aim of this paper is to construct quality control chart with an application, and using Coefficient of Variation Control Chart based on Median Absolute Deviation. It is concluded that in this study, the process was under control for both cases (phase .1 and phase .2), because all points were fallen within the control limits, which means the product meets the required specifications in (phase-1). We also found that the robust Coefficient of Variation control charts based on Median Absolute Deviation can be used as an alternative instead of Coefficient of Variation Control Chart based on (S.D).